TRANSITIONS TO ADULTHOOD OF SECOND-GENERATION YOUTH OF MEXICAN ORIGIN IN ORANGE AND LOS ANGELES COUNTIES (CALIFORNIA): FAMILY TRAJECTORIES - Narváez Jiménez, María del Rosario (2022)
The aim of this article is to find out how the processes of transition to adulthood develop among second-generation young people of Mexican origin, taking the family rajectory as a reference. The biographical approach, specifically the ethno-sociological perspective of Daniel Bertaux, through life stories, has been the technique used. The fieldwork was carried out in 2016 in the counties of Orange and Los Angeles. Among the most relevant aspects the young people highlight in their stories: motherhood/paternity as an event that initiates transitions and its influence on educational and employment trajectories; the gender inequalities that occur as a result of this event; the difficulties in residing independently from parents and the change in intergenerational relationships; as well as the expectations of new parents regarding their children’s education, particularly in terms of language.